2014
DOI: 10.1002/ange.201403192
|View full text |Cite
|
Sign up to set email alerts
|

Activation Energies Control the Macroscopic Properties of Physically Cross‐Linked Materials

Abstract: Here we show the preparation of a series of water‐based physically cross‐linked polymeric materials utilizing cucurbit[8]uril (CB[8]) ternary complexes displaying a range of binding, and therefore cross‐linking, dynamics. We determined that the mechanical strength of these materials is correlated directly with a high energetic barrier for the dissociation of the CB[8] ternary complex cross‐links, whereas facile and rapid self‐healing requires a low energetic barrier to ternary complex association. The versatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
(45 reference statements)
1
22
0
Order By: Relevance
“…liquid-liquid or soft matter interfaces, which is of great relevance in all biological systems 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…liquid-liquid or soft matter interfaces, which is of great relevance in all biological systems 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…[15] NFC has been used for a wide range of emerging applications, such as high-strength nanomaterials and biomedical scaffolds. [16][17][18][19][20] NFC is extracted from plant cell walls and has high elastic moduli (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) and tensile strength in the GPa range. [21][22][23] Dispersed NFC forms stiff hydrogels that are thought to be mediated by fibril-fibril entanglement facilitated by hydrogen bonding.…”
Section: Recentlynaturalstructuralmaterialshaveinspiredsyntheticmentioning
confidence: 99%
“…[26,27] Specifically, the hostguest interactions of cucurbit [8]uril (CB [8]) display reversible complexation at rates approaching the diffusion limit. [28] CB [8] can form 1:1:1 heteroternary complexes with two guest motifs, still allowing very high binding constants in spite of the dynamic nature. In this study, first-guest methylviologen (MV) and second-guest naphthyl (Np) functional polymers were used.…”
Section: Recentlynaturalstructuralmaterialshaveinspiredsyntheticmentioning
confidence: 99%
“…Analogous studies aimed at understanding the effect of crosslink kinetics on viscoelastic material responses have been performed for a number of synthetic polymeric materials. Besides investigating the effect of the crosslink properties themselves (Yount et al, 2005;Shen et al, 2007;Appel et al, 2014;Rossow et al, 2014;Grindy et al, 2015;Tunn et al, 2018), these studies have focused on the contributions of network defects such as dangling ends and loops (Annable et al, 1993;Rossow et al, 2014;Ciarella et al, 2018), crosslink functionality (Li et al, 2016;Gu et al, 2018;Tunn et al, 2019) and polymer length (Annable et al, 1993;Tan et al, 2017). Even though a direct comparison is difficult due to the different polymers used, it can generally be concluded that the number of elastically active chains and their ability to relax after crosslink dissociation are key parameters that determine the macroscopic relaxation time of a material.…”
Section: Introductionmentioning
confidence: 99%